Mitigation and adaptation measures in the hungarian rural development programme - Lazányi, János (Acta Agraria Debreceniensis, 2010)
In the Hungarian Rural Development Programme (RDP) climate change adaptation is addressed through the measures in Axis 1, 2, 3 and 4. Under Axis 1 farmers can receive support for farm modernisation that will help them adapt to climate change. The processing industry will also be able to use the available resources for capital expenditure on buildings and new equipment. Axis 2 and especially the soil and water package within the agrienvironmentalmeasure aim to support production methods, which protect soil quality and will help adaptation to climate change. Measures of Axis 3, such as basic services for the economy and rural population, village renewal and development will provide local communities the opportunity to identify actions that can be undertaken to deal with the effects of climate change. On the other hand, the extension of forest resources contributes to climate change mitigation and enhances carbon sequestration. New methods have been elaborated to the sustainable regional water management, irrigation, water regulation, defence against internal water, and soil protection established. Water management contributes to the balance of water quantity on one side, but also to mitigating the climate change on the other.